2019
DOI: 10.1084/jem.20181936
|View full text |Cite
|
Sign up to set email alerts
|

Use of nonsteroidal anti-inflammatory drugs predicts improved patient survival for PIK3CA-altered head and neck cancer

Abstract: PIK3CA is the most commonly altered oncogene in head and neck squamous cell carcinoma (HNSCC). We evaluated the impact of nonsteroidal anti-inflammatory drugs (NSAIDs) on survival in a PIK3CA-characterized cohort of 266 HNSCC patients and explored the mechanism in relevant preclinical models including patient-derived xenografts. Among subjects with PIK3CA mutations or amplification, regular NSAID use (≥6 mo) conferred markedly prolonged disease-specific survival (DSS; hazard ratio 0.23, P = 0.0032, 95% CI 0.09… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 26 publications
3
58
2
Order By: Relevance
“…For example, 35% expressing dysregulation in the PI3K pathway, a putative site of action of PBM in OSCC. 100 Animal and clinical trials allow assessment of the effect of PBM on the tumor and the tumor microenvironment (e.g. immune function, the surface microenvironment, and epithelial and connective tissue interactions).…”
Section: Discussionmentioning
confidence: 99%
“…For example, 35% expressing dysregulation in the PI3K pathway, a putative site of action of PBM in OSCC. 100 Animal and clinical trials allow assessment of the effect of PBM on the tumor and the tumor microenvironment (e.g. immune function, the surface microenvironment, and epithelial and connective tissue interactions).…”
Section: Discussionmentioning
confidence: 99%
“…However, differential response of PIK3CA-mutated vs. WT tumors, to PI3K-targeted therapies, remains controversial in HNSCC. While one study revealed no association between PIK3CA and responsiveness to PI3K-targeted drugs [94], another group reported PIK3CA mutations to be associated with potential benefit from matched targeted therapy in parathyroid carcinoma [95]. In a recent study evaluating the effect of nonsteroidal anti-inflammatory drugs (NSAID) on survival in head and neck cancer, patients with PIK3CA mutations or amplification showed prolonged disease-specific survival and overall survival with NSAID use as compared with non-NSAID users [96].…”
Section: Pik3ca Gene Mutations Frequency In Head and Neck Squamous Cementioning
confidence: 99%
“…[7][8][9][10][11] Recently, however, Hedberg et al found that regular NSAID use at any time improves disease-specific survival (DSS) and overall survival (OS) in patients with PI3K-altered HNSCC. 12 Less explored is the association of NSAID use with definitive chemoradiation therapy (CRT). This cohort study was performed using a large single institution HNSCC database to further examine the survival outcomes associated with NSAID use during CRT.…”
Section: Introductionmentioning
confidence: 99%